Pola Bakteri Aerob dan Uji Sensitivitas Antibiotik pada Pasien dengan Kateter Uretra di Instalasi Rawat Inap Rumah Sakit Umum Gmim Pancaran Kasih Manado - Theofani Valentino Moniung; Fredine Esther Silvana Rares; Olivia Amelia Waworuntu (Jurnal Syntax Admiration, 2025)
Urinary Tract Infection (UTI) is a significant health problem, especially in hospitals, where the use of urethral catheters is one of the main risk factors. Catheterization can increase the possibility of infection because it is the entry point for microorganisms into the urinary tract. The use of antibiotics is the main choice in the treatment of UTI, but unwise behavior in its use can cause antibiotic resistance. Objective: This study aims to identify the pattern of aerobic bacteria and test the sensitivity of these bacteria to various types of antibiotics in patients using urethral catheters in the inpatient installation of GMIM Pancaran Kasih Hospital, Manado. Methods: The type of research is descriptive with a cross-sectional design, namely by identifying bacteria using the Gram staining method and biochemical tests and antibiotic sensitivity tests. Results: The results of the study obtained three types of bacteria, namely Bacillus sp., Escherichia coli, and Streptococcus sp, all bacteria are sensitive to meropenem. Conclusion: This study found Bacillus sp, Escherichia coli, and Streptococcus sp. and the most common was Bacillus sp. Bacillus sp and Streptococcus sp were sensitive to meropenem but resistant to Aztreonam, Cefuroxime, and Cefotaxime, while Escherichia coli was sensitive to all antibiotics tested.